The 2022 European Union report on pesticide residues in food - European Food Safety Authority (EFSA); Luis Carrasco Cabrera; Giulio Di Piazza; Bruno Dujardin; Emanuela Marchese; Paula Medina Pastor (EFSA Journal, 2024)
Abstract Under European Union legislation (Article 32, Regulation (EC) No 396/2005), the European Food Safety Authority provides an annual report assessing the pesticide residue levels in foods on the European market. In 2022, 96.3% of the overall 110,829 samples analysed fell below the maximum residue level (MRL), 3.7% exceeded this level, of which 2.2% were non‐compliant, i.e. results in a given sample exceeded the MRL after taking into account the measurement uncertainty. For the EU‐coordinated multiannual control programme subset, 11,727 samples were analysed of which 0.9% were non‐compliant. To assess acute and chronic risk to consumer health, dietary exposure to pesticide residues was estimated and compared with available health‐based guidance values (HBGV). Continuation of the probabilistic assessment methodology was consolidated to all pesticides listed in the 2022 EU Regulation providing the probability of a consumer being exposed to an exceedance of the HBGV. Overall, the assessed risk to EU consumer's health is low. Recommendations to risk managers are given to increase the effectiveness of European control systems and to ensure a high level of consumer protection throughout the EU.